Relationship between macroeconomic variables and Malaysia available shariah indices - Mat Isa, Norshamshina; Hasan, Zunairah; Abdullah, Azrul (2012)
This paper aims to study the relationship between some selected macroeconomic variables and Malaysia shariah indices. In our study, we used the Vector Error Correction (VEC) framework by initially looking at the long run and short run relationship between Malaysia available Shariah indices (i.e. KLSI, FTSE bursa Malaysia EMAS Shariah Index and FTSE Bursa Malaysia Hijrah Shariah Index) and the macroeconomic variables via the Johansen cointegration technique. Monthly data during the twenty two-year period between 1990 and december 2011 has been collected from DataStream and tested. The findings successfully establish the existence of relationship between the variables.